Hidup Selibat demi Kerajaan Allah dalam Perspektif Teologi Tubuh Yohanes Paulus II - Alb Irawan Dwiatmaja (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
Abstract: This paper proposes a new way of understanding celibacy. The world offers that the most important thing is an active and free life, that is, one cannot be a complete and warm human being in a relationshipwithout a genital sexual experience. The world underestimates celibacy and wants to prove that the choice of celibate life will result in compensation secretly, illegally, and will lead to destructive and manipulative relationships. The thoughts of John Paul II are relevant in an effort to offer a paradigm of sexual liberation, to develop, and to maintain for the creation of sexuality values and the call to life for the sake of the Kingdom of God. John Paul II’s thoughts on celibacy for the sake of the Kingdom of God in the perspective of theology of the body become material for reflection and input for people who live celibate to live in harmony with all the complexities of their bodies. Keywords: Celibacy, John Paul II, Kingdom of God, theology of the body, Rome Catholic.